Elaborate Isolation: Metastructures of Knowledge About Women - PALMER, Carole L; MALONE, Cheryl Knott (The Information society, 2001)
This paper examines the category of "Woman" within the metastructure of a system of knowledge organization. We trace the subject scheme used to list books about women in a standard bibliographic guide over the first three-quarters of the twentieth century.Building on the feminist critique of subject representation, our analysis documents how the category was continually constructed over time, providing evidence of multiplication, isolation, and confusion in the process. The outcome is a framework that fails to capture the complex nature of knowledge about women and conceals relationships to the larger body of knowledge. The case of this legacy system exemplifies problems associated with representing the complexity and integration of knowledge and provides a basis for considering the potential residual impacts of current information organization and navigation systems.